TANGGAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) VARIETAS KUNING TERHADAP PEMBERIAN KOMPOS KASCING DAN PUPUK NPK - Natasya Sembiring; B. Sengli J. Damanik; Jonatan Ginting (Universitas Sumatera Utara, 2013)
Growth Response and Production of Shallot (Allium ascalonicum L.) Kuning Variety WithApplication of Vermicompost and NPK Fertilizer, supervised by B. Sengli J. Damanik andJonatan Ginting. The research was conducted at Pasar 1 street Tanjung Sari, began Juny untilAugust 2012, by using a Randomized Block Design with two factors. First factor is Vermicompostdoses that is 0, 10, 20, and 30 g/plant, the second factor NPK fertilize (16:16:16) doses that is 0;14,1; 28,2; 42,3 and 56,4 g/plot (1m2). The parameters observed were plant height, tiller number,leaf number, fresh weight bulb per sample, dry weight bulb per sample, fresh weight bulb per plot,dry weight bulb per plot,and clove number per sample. The results showed that the treatment ofvermicompost had no significant effects on all parameters observed. The NPK fertilize significantlyinfluenced on dry weight per plot.Key words : vermicompost, NPK, shallot